Preparation method of flexible and recyclable polyphenol-based solid-solid phase change material
By using polyethylene glycol and hexamethylene diisocyanate in solid-solid phase change materials, and combining chain extension and crosslinking of melamine, tannin and ferric chloride, a dynamic crosslinking network and coordination crosslinking network are formed, the problem that the material cannot be flexible, thermal stability and recyclable at the same time, and the flexibility, thermal stability and recyclability of the material are achieved, and it is suitable for a wide range of and long-term applications in the field of thermal management.
Patent Information
- Application Number
- CN202411726724.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-03-04
AI Technical Summary
Existing solid-solid phase change materials cannot be flexible, thermal stability and recyclable at the same time, and are difficult to be widely used in the field of thermal management.
Through the reaction of polyethylene glycol and hexamethylene diisocyanate in DMF, the chain extension and crosslinking of melamine, tannic acid and ferric chloride are combined to form a dynamic crosslinking network and coordination crosslinking network, which gives the material flexibility and recyclability.
The flexibility and thermal stability of the material are achieved, and at the same time they have recyclable and reprocessable properties, and can use the phase change mechanism to store solar energy and reprocess it according to the application scenario.
Smart Images

Figure CN119552343A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of phase change energy storage materials. Background Art
[0002] Phase change materials can store or release a large amount of latent heat during the phase change process without the need for additional resource consumption, and are often used in the field of thermal management as clean and efficient temperature control materials. Usually, phase change materials change between rigid solid and flowing liquid states during the phase change process. However, in actual application environments, rigid solids are difficult to use on complex surfaces such as joints and curved surfaces, and the leakage of flowing liquid after the phase change will reduce the thermal management capability. Therefore, there is an urgent need to develop a solid-solid phase change material that is flexible and does not leak during phase change.
[0003] Generally, solid-solid phase change materials synthesized by chemical methods show better flexibility and thermal stability due to the formation of covalent bonds. However, solid-solid phase change materials with permanent cross-linked structures are usually difficult to recycle or reprocess into other shapes after damage, resulting in waste of resources and economic burden. Therefore, designing a solid-solid phase change material that combines recyclability and flexibility is crucial for widespread and long-term applications in thermal management. Summary of the invention
[0004] The present invention aims to solve the problem that existing solid-solid phase change materials cannot have flexibility, thermal stability and recyclability at the same time, and further provides a method for preparing a flexible and recyclable polyphenol-based solid-solid phase change material.
[0005] A method for preparing a flexible and recyclable polyphenol-based solid-solid phase change material is carried out according to the following steps:
[0006] 1. dissolving polyethylene glycol and hexamethylene diisocyanate in DMF, heating and stirring to react under a dry nitrogen environment to obtain a reaction system;
[0007] 2. In a dry nitrogen environment, the reaction system is cooled, and then melamine and tannic acid are added, and the temperature is raised and heated and stirred to react to obtain a reaction system after chain extension and cross-linking;
[0008] 3. Under a dry nitrogen environment, the reaction system after chain extension and cross-linking is cooled down, and then ferric chloride is added, and the temperature is raised and heated and stirred to react to obtain a uniform blue-black solution;
[0009] Fourth, the uniform blue-black solution is dried and solidified, thereby completing the preparation method of the flexible and recyclable polyphenol-based solid-solid phase change material.
[0010] The beneficial effects of the present invention are:
[0011] 1. The terminal hydroxyl group of polyethylene glycol and the terminal isocyanate group of hexamethylene diisocyanate can react to form a strong urethane bond, and realize a covalent cross-linking network through chain extension cross-linking of the amino group of melamine and the phenolic hydroxyl group of tannic acid, which gives the material excellent mechanical properties and realizes solid-solid phase change properties.
[0012] 2. The phenolic hydroxyl groups of tannic acid can react with the isocyanate groups in hexamethylene diisocyanate to form dynamically cross-linked phenol-urethane bonds, which can be broken or reorganized at a certain temperature, giving the material recyclable and reprocessable properties.
[0013] 3. The iron ions in ferric chloride can react with the phenolic hydroxyl groups of tannic acid to form a complex, forming a coordination cross-linking network in the solid-solid phase change material, which improves the mechanical properties of the material while giving the material photothermal properties under near-infrared light.
[0014] 4. Combining the phase change properties and photothermal properties of the material, the prepared flexible and recyclable polyphenol-based solid-solid phase change material can store and utilize solar energy using the phase change mechanism, and can be reprocessed into the desired shape according to the application scenario.
[0015] Attached Notes
[0016] Figure 1 The synthetic route for preparing a flexible and recyclable polyphenol-based solid-solid phase change material according to Example 1;
[0017] Figure 2 The actual picture of the flexible and recyclable polyphenol-based solid-solid phase change material prepared in Example 1, a is the original picture, b is the actual picture after bending, and c is the actual picture after folding into a windmill;
[0018] Figure 3 FTIR infrared spectrum of the flexible and recyclable polyphenol-based solid-solid phase change material prepared in Example 1-9;
[0019] Figure 4 The tensile test curve of the flexible and recyclable polyphenol-based solid-solid phase change material prepared in Examples 1-9;
[0020] Figure 5 A comparison diagram of the phase change process of the flexible and recyclable polyphenol-based solid-solid phase change material prepared in Example 1 and polyethylene glycol 10000;
[0021] Figure 6 POM images of the flexible and recyclable polyphenol-based solid-solid phase change material prepared in Example 1; a is before crystallization, b is during crystallization, and c is after crystallization;
[0022] Figure 7 DSC curves of the flexible and recyclable polyphenol-based solid-solid phase change materials prepared in Examples 1-9; a is an exothermic process, and b is an endothermic process;
[0023] Figure 8 The UV-visible-near infrared absorption spectra of the flexible and recyclable polyphenol-based solid-solid phase change materials prepared in Examples 1 and 7-9;
[0024] Fig. 9 The temperature rise curves of the flexible and recyclable polyphenol-based solid-solid phase change materials prepared in Examples 1 and 7-9 under light illumination;
[0025] Fig.10 Thermal imaging effect diagram of the flexible and recyclable polyphenol-based solid-solid phase change material prepared in Examples 1 and 7-9 under illumination;
[0026] Fig.11 The photothermal cycle heating and cooling curve of the flexible and recyclable polyphenol-based solid-solid phase change material prepared in Example 9;
[0027] Fig.12 This is a physical picture of the thermal repair performance of the flexible and recyclable polyphenol-based solid-solid phase change material prepared in Example 9;
[0028] Fig.13 This is a cyclic performance test of three thermal repairs of the flexible and recyclable polyphenol-based solid-solid phase change material prepared in Example 9. a is a tensile test, b is a DSC curve, and c is a temperature rise and fall curve under light. DETAILED DESCRIPTION
[0029] Specific embodiment 1: This embodiment is a method for preparing a flexible and recyclable polyphenol-based solid-solid phase change material, which is carried out according to the following steps:
[0030] 1. dissolving polyethylene glycol and hexamethylene diisocyanate in DMF, heating and stirring to react under a dry nitrogen environment to obtain a reaction system;
[0031] 2. In a dry nitrogen environment, the reaction system is cooled, and then melamine and tannic acid are added, and the temperature is raised and heated and stirred to react to obtain a reaction system after chain extension and cross-linking;
[0032] 3. Under a dry nitrogen environment, the reaction system after chain extension and cross-linking is cooled down, and then ferric chloride is added, and the temperature is raised and heated and stirred to react to obtain a uniform blue-black solution;
[0033] Fourth, the uniform blue-black solution is dried and solidified, thereby completing the preparation method of the flexible and recyclable polyphenol-based solid-solid phase change material.
[0034] The solvent N,N-dimethylformamide (DMF) described in step 1 of this embodiment has a boiling point (153° C.) much higher than the synthesis temperature, so the reflux equipment is omitted to simplify the device.
[0035] The beneficial effects of this embodiment are:
[0036] 1. The terminal hydroxyl group of polyethylene glycol and the terminal isocyanate group of hexamethylene diisocyanate can react to form a strong urethane bond, and realize a covalent cross-linking network through chain extension cross-linking of the amino group of melamine and the phenolic hydroxyl group of tannic acid, which gives the material excellent mechanical properties and realizes solid-solid phase change properties.
[0037] 2. The phenolic hydroxyl groups of tannic acid can react with the isocyanate groups in hexamethylene diisocyanate to form dynamically cross-linked phenol-urethane bonds, which can be broken or reorganized at a certain temperature, giving the material recyclable and reprocessable properties.
[0038] 3. The iron ions in ferric chloride can react with the phenolic hydroxyl groups of tannic acid to form a complex, forming a coordination cross-linking network in the solid-solid phase change material, which improves the mechanical properties of the material while giving the material photothermal properties under near-infrared light.
[0039] 4. Combining the phase change properties and photothermal properties of the material, the prepared flexible and recyclable polyphenol-based solid-solid phase change material can store and utilize solar energy using the phase change mechanism, and can be reprocessed into the desired shape according to the application scenario.
[0040] Specific embodiment 2: This embodiment is different from specific embodiment 1 in that the polyethylene glycol described in step 1 is the polyethylene glycol after vacuum dehydration, and the vacuum dehydration is specifically carried out at a temperature of 80°C to 90°C for 8h to 12h; the DMF described in step 1 is the DMF after molecular sieve dehydration. The rest is the same as specific embodiment 1.
[0041] Specific implementation method 3: This implementation method is different from specific implementation method 1 or 2 in that the molecular weight of the polyethylene glycol described in step 1 is 4000 to 10000. The rest is the same as specific implementation method 1 or 2.
[0042] Specific embodiment 4: This embodiment is different from specific embodiments 1 to 3 in that: the molar ratio of polyethylene glycol to hexamethylene diisocyanate in step 1 is 1:(2-2.2); the mass ratio of polyethylene glycol to DMF in step 1 is 1 g:(1-4) mL. Others are the same as specific embodiments 1 to 3.
[0043] Specific embodiment 5: This embodiment differs from specific embodiments 1 to 4 in that: in step 1, the temperature is 80°C to 85°C, the stirring speed is 800r / min to 1000r / min, and the reaction is heated and stirred for 2h to 4h in a dry nitrogen environment. The rest is the same as specific embodiments 1 to 4.
[0044] Specific embodiment 6: This embodiment differs from specific embodiments 1 to 5 in that: the molar ratio of melamine to tannic acid in step 2 is 1:(0.5-2); the total molar amount of the amino groups in melamine and the phenolic hydroxyl groups in tannic acid in step 2 is equal to the total molar amount of the isocyanate remaining in the reaction in step 1. The rest is the same as specific embodiments 1 to 5.
[0045] Specific embodiment 7: This embodiment differs from specific embodiments 1 to 6 in that: in step 2, the reaction system is cooled to 60°C to 65°C under a dry nitrogen environment, and then melamine and tannic acid are added, and then the temperature is raised to 80°C to 85°C at a heating rate of 2°C / min to 3°C / min, and the reaction is heated and stirred for 2h to 4h at a temperature of 80°C to 85°C, a stirring speed of 800r / min to 1000r / min and a dry nitrogen environment. The rest is the same as specific embodiments 1 to 6.
[0046] Specific embodiment 8: This embodiment differs from Specific embodiments 1 to 7 in that the mass of the ferric chloride described in step 3 is 0.5% to 5% of the solid content in the reaction system after chain extension and cross-linking. The rest is the same as Specific embodiments 1 to 7.
[0047] Specific embodiment 9: This embodiment is different from specific embodiments 1 to 8 in that: in step 3, the reaction system after chain extension and cross-linking is cooled to 60°C to 65°C under a dry nitrogen environment, and then ferric chloride is added, and then the temperature is increased to 80°C to 85°C at a heating rate of 2°C / min to 3°C / min, and the reaction is heated and stirred for 2h to 4h at a temperature of 80°C to 85°C, a stirring speed of 800r / min to 1000r / min and a dry nitrogen environment. The rest is the same as specific embodiments 1 to 8.
[0048] Specific embodiment 10: This embodiment differs from Specific embodiments 1 to 9 in that the drying and curing described in step 4 is specifically performed at a temperature of 60° C. to 90° C. and vacuum drying and curing for 10 to 12 hours. The rest is the same as Specific embodiments 1 to 9.
[0049] The following examples are used to verify the beneficial effects of the present invention:
[0050] Embodiment 1:
[0051] A method for preparing a flexible and recyclable polyphenol-based solid-solid phase change material is carried out according to the following steps:
[0052] 1. Dissolve 25 g of polyethylene glycol and 0.84 g of hexamethylene diisocyanate (the molar ratio of polyethylene glycol to hexamethylene diisocyanate is 1:2) in 40 mL of DMF, and heat and stir for 4 h at 80° C. and 900 r / min in a dry nitrogen environment to obtain a reaction system;
[0053] The molecular weight of the polyethylene glycol is 10000;
[0054] 2. Under a dry nitrogen environment, the reaction system was cooled to 60°C, and then 0.10 g of melamine and 0.27 g of tannic acid (the molar ratio of melamine to tannic acid was 1:1) were added, and then the temperature was raised to 80°C at a heating rate of 3°C / min, and heated and stirred for 4 hours at a temperature of 80°C, a stirring speed of 900 r / min and a dry nitrogen environment to obtain a reaction system after chain extension and cross-linking;
[0055] The total molar amount of the amino groups in the melamine and the phenolic hydroxyl groups in the tannic acid is equal to the total molar amount of the isocyanate remaining in the reaction in step 1;
[0056] 3. Under a dry nitrogen environment, the reaction system after chain extension and cross-linking was cooled to 60°C, and then 0.26g of ferric chloride was added (the mass of ferric chloride was 1% of the solid content in the reaction system after chain extension and cross-linking), and then the temperature was raised to 80°C at a heating rate of 3°C / min, and the reaction was heated and stirred for 2h at a temperature of 80°C, a stirring speed of 900r / min and a dry nitrogen environment to obtain a uniform blue-black solution;
[0057] 4. Under the condition of temperature of 80°C, the uniform blue-black solution was vacuum dried and solidified for 12 hours to obtain a flexible and recyclable polyphenol-based solid-solid phase change material.
[0058] The polyethylene glycol described in step 1 is the polyethylene glycol after vacuum dehydration, and the vacuum dehydration is specifically carried out at a temperature of 80° C. for 24 hours; the DMF described in step 1 is the DMF after molecular sieve dehydration.
[0059] Example 2: This example is different from Example 1 in that: the molecular weight of the polyethylene glycol described in step 1 is 4000; the amount of polyethylene glycol used in step 1 is 20 g, the amount of hexamethylene diisocyanate used is 1.68 g, that is, the molar ratio of polyethylene glycol to hexamethylene diisocyanate is 1:2; the amount of melamine used in step 2 is 0.20 g, the amount of tannic acid used is 0.55 g, that is, the molar ratio of melamine to tannic acid is 1:1; the amount of ferric chloride used in step 3 is 0.22 g, that is, the mass of ferric chloride is 1% of the solid content in the reaction system after chain extension and cross-linking. Others are the same as Example 1.
[0060] Example 3: This example is different from Example 1 in that: the molecular weight of the polyethylene glycol described in step 1 is 6000; the amount of polyethylene glycol used in step 1 is 30 g, the amount of hexamethylene diisocyanate used is 1.68 g, that is, the molar ratio of polyethylene glycol to hexamethylene diisocyanate is 1:2; the amount of melamine used in step 2 is 0.20 g, the amount of tannic acid used is 0.55 g, that is, the molar ratio of melamine to tannic acid is 1:1; the amount of ferric chloride used in step 3 is 0.32 g, that is, the mass of ferric chloride is 1% of the solid content in the reaction system after chain extension and cross-linking. Others are the same as Example 1.
[0061] Example 4: This example is different from Example 1 in that: the molecular weight of the polyethylene glycol described in step 1 is 8000; the amount of polyethylene glycol used in step 1 is 20 g, the amount of hexamethylene diisocyanate used is 0.84 g, that is, the molar ratio of polyethylene glycol to hexamethylene diisocyanate is 1:2; the amount of melamine used in step 2 is 0.10 g, the amount of tannic acid used is 0.27 g, that is, the molar ratio of melamine to tannic acid is 1:1; the amount of ferric chloride used in step 3 is 0.21 g, that is, the mass of ferric chloride is 1% of the solid content in the reaction system after chain extension and cross-linking. Others are the same as Example 1.
[0062] Example 5: This example is different from Example 1 in that: the molecular weight of the polyethylene glycol described in step 1 is 10000; the amount of polyethylene glycol used in step 1 is 25g, the amount of hexamethylene diisocyanate used is 0.84g, that is, the molar ratio of polyethylene glycol to hexamethylene diisocyanate is 1:2; the amount of melamine used in step 2 is 0.13g, the amount of tannic acid used is 0.18g, that is, the molar ratio of melamine to tannic acid is 1:0.5; the amount of ferric chloride used in step 3 is 0.26g, that is, the mass of ferric chloride is 1% of the solid content in the reaction system after chain extension and cross-linking. Others are the same as Example 1.
[0063] Example 6: This example is different from Example 1 in that: the molecular weight of the polyethylene glycol described in step 1 is 10000; the amount of polyethylene glycol used in step 1 is 25g, the amount of hexamethylene diisocyanate used is 0.84g, that is, the molar ratio of polyethylene glycol to hexamethylene diisocyanate is 1:2; the amount of melamine used in step 2 is 0.07g, the amount of tannic acid used is 0.37g, that is, the molar ratio of melamine to tannic acid is 1:2; the amount of ferric chloride used in step 3 is 0.26g, that is, the mass of ferric chloride is 1% of the solid content in the reaction system after chain extension and cross-linking. Others are the same as Example 1.
[0064] Example 7: This example is different from Example 1 in that: the molecular weight of the polyethylene glycol described in step 1 is 10000; the amount of polyethylene glycol used in step 1 is 25g, the amount of hexamethylene diisocyanate used is 0.84g, that is, the molar ratio of polyethylene glycol to hexamethylene diisocyanate is 1:2; the amount of melamine used in step 2 is 0.10g, the amount of tannic acid used is 0.27g, that is, the molar ratio of melamine to tannic acid is 1:1; the amount of ferric chloride used in step 3 is 0.13g, that is, the mass of ferric chloride is 0.5% of the solid content in the reaction system after chain extension and cross-linking. Others are the same as Example 1.
[0065] Example 8: This example is different from Example 1 in that: the molecular weight of the polyethylene glycol described in step 1 is 10000; the amount of polyethylene glycol used in step 1 is 25g, the amount of hexamethylene diisocyanate used is 0.84g, that is, the molar ratio of polyethylene glycol to hexamethylene diisocyanate is 1:2; the amount of melamine used in step 2 is 0.10g, the amount of tannic acid used is 0.27g, that is, the molar ratio of melamine to tannic acid is 1:1; the amount of ferric chloride used in step 3 is 0.52g, that is, the mass of ferric chloride is 2% of the solid content in the reaction system after chain extension and cross-linking. Others are the same as Example 1.
[0066] Example 9: This example is different from Example 1 in that: the molecular weight of the polyethylene glycol described in step 1 is 10000; the amount of polyethylene glycol used in step 1 is 25g, the amount of hexamethylene diisocyanate used is 0.84g, that is, the molar ratio of polyethylene glycol to hexamethylene diisocyanate is 1:2; the amount of melamine used in step 2 is 0.10g, the amount of tannic acid used is 0.27g, that is, the molar ratio of melamine to tannic acid is 1:1; the amount of ferric chloride used in step 3 is 1.31g, that is, the mass of ferric chloride is 5% of the solid content in the reaction system after chain extension and cross-linking. Others are the same as Example 1.
[0067] Figure 1 The present invention is a synthetic route for preparing a flexible and recyclable polyphenol-based solid-solid phase change material according to Example 1; a terminal hydroxyl group of polyethylene glycol is reacted with a diisocyanate to generate a terminal isocyanate group prepolymer, which is further chain extended and cross-linked through the amino group of melamine and the phenolic hydroxyl group of tannic acid, and the excess catechol structure of tannic acid is used to form a coordination bond with trivalent iron ions to achieve complex cross-linking, and finally a finished product is obtained.
[0068] Figure 2 This is a physical picture of the flexible and recyclable polyphenol-based solid-solid phase change material prepared in Example 1, a is the original picture, b is the physical picture after bending, and c is the physical picture after folding into a windmill; it can be seen from the figure that its black appearance comes from the complex formed by tannic acid and trivalent iron ions, bc shows the flexibility of the material given by the chemical cross-linking structure produced after synthesis.
[0069] Figure 3 FTIR infrared spectrum of the flexible and recyclable polyphenol-based solid-solid phase change material prepared in Example 1-9; as can be seen from the figure, at 3300 and 1540 cm -1 A clear imine structure can be observed nearby at 1720 cm -1 There is a carbonyl structure in the urethane group nearby, and 1600cm -1 The benzene ring structure in tannic acid nearby demonstrates the successful synthesis of solid-solid phase change materials.
[0070] Conduct tensile test according to GB_T 1040 standard; Figure 4 The tensile test curves of the flexible and recyclable polyphenol-based solid-solid phase change materials prepared in Examples 1-9; it can be seen from Examples 1-4 that with the increase of the molecular weight of polyethylene glycol, the soft segment molecular chain grows, the tensile strength of the material is 14.3-17.3 MPa, and the elongation at break is 350-545%, both of which increase with the increase of the molecular weight of polyethylene glycol; it can be seen from Examples 1, 5-6 that when the ratio of tannic acid to melamine increases, the dynamic covalent bond ratio increases, the tensile strength of the material is 15.5-17.3 MPa, and the elongation at break is 487-626%, which decreases slightly with the increase of the tannic acid ratio; it can be seen from Examples 1, 7-9 that with the increase of the ferric chloride content, the coordination cross-linking sites of polyphenol-metal increase, the tensile strength of the material is 15.3-25.1 MPa, which increases with the increase of the iron ion content; the elongation at break is 250-922%, which decreases with the increase of the iron ion content.
[0071] Table 1 is a table of mechanical properties test results of the examples
[0072]
[0073] Figure 5 This is a comparison diagram of the phase change process of the flexible and recyclable polyphenol-based solid-solid phase change material prepared in Example 1 and polyethylene glycol 10000; as can be seen from the figure, after being placed on a heating platform at 80°C for 20 minutes, the polyethylene glycol phase changes to a liquid state in the later stage, while Example 1 remains solid after the phase change, demonstrating good thermal stability and verifying the solid-solid phase change performance.
[0074] The flexible and recyclable polyphenol-based solid-solid phase change material prepared in Example 1 was heated to 80° C., and placed under a polarizing microscope to take images before crystallization (80° C.), during crystallization (40° C.), and after crystallization (25° C.) during the cooling process; Figure 6 POM images of the flexible and recyclable polyphenol-based solid-solid phase change material prepared in Example 1; a is before crystallization, b is during crystallization, and c is after crystallization. As can be seen from the figure, as the temperature decreases below the phase change temperature, spherulites gradually appear in the phase change material, confirming the crystallization performance of the material at the phase change temperature.
[0075] Figure 7 DSC curves of the flexible and recyclable polyphenol-based solid-solid phase change materials prepared in Examples 1-9; a is an exothermic process, and b is an endothermic process; as can be seen from the figure and Table 2, with the increase of the molecular weight of polyethylene glycol, the phase change temperature range and the phase change enthalpy also increase; with the increase of the ratio of tannic acid to melamine, the phase change enthalpy of the material also increases; when the content of added ferric chloride increases, the cross-linking network increases, and the phase change enthalpy decreases to a certain extent, which is in line with the experimental expectations.
[0076] Table 2 is the DSC test result data table of the embodiment
[0077]
[0078] Figure 8 The UV-visible-near infrared absorption spectra of the flexible and recyclable polyphenol-based solid-solid phase change materials prepared in Examples 1, 7-9; as can be seen from the figure, as the ferric chloride content increases, the complex in the solid-solid phase change material increases, and the light absorption rate in the near-infrared region is enhanced. In Example 9 where the ferric chloride content is 5%, the minimum absorption rate of the material in the near-infrared region is as high as 60%, confirming the high absorption rate of the material in the near-infrared region.
[0079] The illumination test was performed using a xenon lamp with a light power of 50W and a spectral range of 320 to 2500nm; Fig. 9 The temperature rise curves of the flexible and recyclable polyphenol-based solid-solid phase change materials prepared in Examples 1, 7-9 under light illumination; as can be seen from the figure, as the ferric chloride content increases, the material's absorption rate of near-infrared light increases, the temperature rises faster, and the temperature that can be reached is also higher. In Example 9 with a ferric chloride content of 5%, the material can reach a maximum temperature of 54°C within 300s, confirming the photothermal performance of the solid-solid phase change material.
[0080] The illumination test was performed using a xenon lamp with a light power of 50W and a spectral range of 320 to 2500nm; Fig.10 The thermal imaging effect diagram of the flexible and recyclable polyphenol-based solid-solid phase change material prepared in Examples 1 and 7-9 under illumination; as can be seen from the figure, as the ferric chloride content increases from 0.5% to 5%, the temperature reached by the material after 5 minutes of illumination increases from 41°C to 54°C, confirming the photothermal performance of the solid-solid phase change material.
[0081] A xenon lamp with a light power of 50W and a spectral range of 320-2500nm was used for the light cycle test, in which one light cycle consisted of 300s of illumination followed by turning off the light source and cooling for 300s. Fig.11This is the photothermal cyclic heating and cooling curve of the flexible and recyclable polyphenol-based solid-solid phase change material prepared in Example 9; as can be seen from the figure, after 10 photothermal cycles, Example 9 with a ferric chloride content of 5% can still reach 51.3°C within 300s of illumination, confirming the good cyclic stability of the material.
[0082] Use a hot press to perform a heat repair test: cut the material into pieces and heat press at 120°C with a pressure of 5 MPa for 5 minutes as one heat repair cycle; Fig.12 This is a physical picture of the thermal repair performance of the flexible and recyclable polyphenol-based solid-solid phase change material prepared in Example 9; as can be seen from the figure, given the dynamic cross-linking structure generated by the reaction of tannic acid and isocyanate, the prepared solid-solid phase change material can achieve reversible cross-linking above 120°C. The material can be recycled and reprocessed by means such as hot pressing, which proves the recyclability of the material.
[0083] Conduct tensile test according to GB_T 1040 standard; Fig.13 The flexible and recyclable polyphenol-based solid-solid phase change material prepared in Example 9 was thermally repaired for three cycles. a is the tensile test, b is the DSC curve, and c is the heating and cooling curve under light. It can be seen from the figure that the elongation at break and the maximum tensile strength of the material after three cycles of thermal repair are 219% and 24.9 MPa, respectively, which are 88% and 90% of those before repair, respectively. There is no obvious change in the positions of the endothermic and exothermic peaks of the material after three cycles of thermal repair, and the phase change performance remains at a good level. After three cycles of thermal repair, the material can still reach a temperature of 50.2°C after 5 minutes of light exposure, which confirms the thermal repair performance of the material.
Claims
1. A method for preparing a flexible and recyclable polyphenol-based solid-solid phase change material, characterized in that It is carried out in the following steps:
1. dissolving polyethylene glycol and hexamethylene diisocyanate in DMF, heating and stirring to react under a dry nitrogen environment to obtain a reaction system; 2. In a dry nitrogen environment, the reaction system is cooled, and then melamine and tannic acid are added, and the temperature is raised and heated and stirred to react to obtain a reaction system after chain extension and cross-linking; 3. Under a dry nitrogen environment, the reaction system after chain extension and cross-linking is cooled down, and then ferric chloride is added, and the temperature is raised and heated and stirred to react to obtain a uniform blue-black solution; Fourth, the uniform blue-black solution is dried and solidified, thereby completing the preparation method of the flexible and recyclable polyphenol-based solid-solid phase change material.
2. The method for preparing a flexible and recyclable polyphenol-based solid-solid phase change material according to claim 1, characterized in that The polyethylene glycol described in step 1 is polyethylene glycol after vacuum dehydration, and the vacuum dehydration is specifically performed at a temperature of 80° C. to 90° C. for 8 h to 12 h; the DMF described in step 1 is DMF after molecular sieve dehydration.
3. The method for preparing a flexible and recyclable polyphenol-based solid-solid phase change material according to claim 1, characterized in that The molecular weight of the polyethylene glycol described in step 1 is 4000-10000.
4. The method for preparing a flexible and recyclable polyphenol-based solid-solid phase change material according to claim 1, characterized in that The molar ratio of the polyethylene glycol described in step 1 to hexamethylene diisocyanate is 1:(2-2.2); the volume ratio of the polyethylene glycol described in step 1 to DMF is 1 g:(1-4) mL.
5. The method for preparing a flexible and recyclable polyphenol-based solid-solid phase change material according to claim 1, characterized in that In step 1, the reaction is heated and stirred for 2 h to 4 h at a temperature of 80° C. to 85° C., a stirring speed of 800 r / min to 1000 r / min and a dry nitrogen environment.
6. The method for preparing a flexible and recyclable polyphenol-based solid-solid phase change material according to claim 1, characterized in that The molar ratio of melamine to tannic acid in step 2 is 1:(0.5-2); the total molar amount of the amino groups in the melamine and the phenolic hydroxyl groups in the tannic acid in step 2 is equal to the total molar amount of the isocyanate remaining in the reaction in step 1.
7. The method for preparing a flexible and recyclable polyphenol-based solid-solid phase change material according to claim 1, characterized in that In step 2, under a dry nitrogen environment, the reaction system is cooled to 60°C to 65°C, and then melamine and tannic acid are added, and then the temperature is increased to 80°C to 85°C at a rate of 2°C / min to 3°C / min. The reaction is heated and stirred for 2h to 4h at a temperature of 80°C to 85°C, a stirring speed of 800r / min to 1000r / min and a dry nitrogen environment.
8. The method for preparing a flexible and recyclable polyphenol-based solid-solid phase change material according to claim 1, characterized in that The mass of the ferric chloride described in step three is 0.5% to 5% of the solid content in the reaction system after chain extension and cross-linking.
9. The method for preparing a flexible and recyclable polyphenol-based solid-solid phase change material according to claim 1, characterized in that In step three, under a dry nitrogen environment, the reaction system after chain extension and cross-linking is cooled to 60°C to 65°C, and then ferric chloride is added, and then the temperature is increased to 80°C to 85°C at a heating rate of 2°C / min to 3°C / min. The reaction is heated and stirred for 2h to 4h at a temperature of 80°C to 85°C, a stirring speed of 800r / min to 1000r / min and a dry nitrogen environment.
10. The method for preparing a flexible and recyclable polyphenol-based solid-solid phase change material according to claim 1, characterized in that The drying and curing described in step 4 is specifically to dry and curing in vacuum at a temperature of 60° C. to 90° C. for 10 h to 12 h.